X-linked adrenoleukodystrophy: a clinical case - V. S. Ledneva; A. S. Ivannikova; M. V. Popova; O. I. Kiyatkina; A. A. Tikhonova; N. S. Korchagina (Лечащий Врач)
Background. Adrenoleukodystrophy (ALD) is an orphan hereditary disease associated with severe metabolic disorders. Taking into account the late appearance of symptoms of the disease with irreversible progression, it is relevant to introduce methods of early diagnosis in the newborn period for the timely appointment of effective therapy before the appearance of clinical signs of the disease.Objective. The aim of the study was to describe a clinical case of familial X-linked adrenoleukodystrophy.Materials and methods. The analysis of the child's development histories, medical records of an outpatient patient, and medical records of an inpatient patient of three siblings with X-linked adrenoleukodystrophy was carried out.Results. This article discusses a clinical case of familial adrenoleukodystrophy in three siblings. The older sibling developed symptoms of the disease from an early age in the form of delayed physical and psychomotor development, unexplained bouts of hyperexcitability, and muscle twitching. From the age of three, the symptoms of adrenal insufficiency increased. After a hospital examination, primary adrenal insufficiency was diagnosed and hormone replacement therapy was prescribed. A genetic study that made it possible to diagnose X-linked adrenoleukodystrophy was conducted only at the age of 6 years due to the deterioration of the patient's condition and the increase in neurological symptoms. Two younger siblings had a more favorable course of the disease.Conclusion. The described family case of X-linked adrenoleukodystrophy clearly showed the need to develop methods for early diagnosisof the disease, which determine not only the effectiveness of timely treatment and improvement of the quality of life of patients, but also the possibility of having healthy children.